Metal–Organic Framework Based Catalysts for Hydrogen Evolution - Zhu, Bingjun; Zou, Ruqiang; Xu, Qiang (Advanced Energy Materials, 2018)
Highly efficient hydrogen evolution reactions (HERs) will determine the mass distributions of hydrogen‐powered clean technologies in the future. Metal–organic frameworks (MOFs) are emerging as a class of crystalline porous materials. Along with their derivatives, MOFs have recently been under intense study for their applications in various hydrogen production techniques. MOF‐based materials possess unique advantages, such as high specific surface area, crystalline porous structure, diverse and tunable chemical components, which offer attractive functionalities in catalyzing hydrogen evolution processes, by lowering reaction potentials, and speeding up reaction rates. Considering the rapid increase in research interest in hydrogen evolution in the last several years, this review aims to summarize recent advances in MOF‐associated hydrogen evolution research, including electrocatalytic, photocatalytic, and chemocatalytic HER. Particular attention is paid to the design and utilization of postsynthetic modification of MOFs, MOF‐supported catalysts, and MOF derivatives for highly efficient HER. The opportunities and challenges for MOF‐based materials in a hydrogen‐powered clean future are also discussed. Metal–organic frameworks (MOFs) along with their derivatives are under intensive studies for their applications in various hydrogen evolution reactions (HER). This review summarizes the recent rapid increase in interest in MOF‐associated hydrogen evolution research, including MOFs and their corresponding derivatives for electrocatalytic, photocatalytic, and chemocatalytic HER. The opportunities and challenges for MOF‐based catalysts for future hydrogen production are also discussed in this review.